The centre of mass kinematics for elite women judo athletes in seoi-nage - Ishii, T.; Ae, M.; Koshida, S.; Fujii, N. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate kinematics of the whole body centre of mass (COM) in seoi-nags performed by elite and collegiate women judo athletes. Three dimensional coordinate data were captured using a Vicon-Mx system with 18 cameras operating at 250 Hz as 3 women elite judo athletes and 6 women college level judo athletes performed seoi-nage. No difference was found in motion time of the turning phase in seoi-nage between the two groups, indicating that motion time may not be a factor to determine the skill level of seoi-nage. The maximum Y relative velocity of the COM in seoi-nage was much greater in the elite women judo athletes than the collegiate judo athletes, which implied that the relative forward velocity of the COM would be an index to evaluate the skill level of seoi-nage for women judo athletes.